MICRONUTRIENTS AND CHILDREN'S PHYSICAL GROWTH: A META ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - R.T. Saygitov ("Paediatrician" Publishers LLC, 2008)
The data from 12 randomized controlled trials (over 4 thousand of children with known anthropometric data), investigating efficacy of supplement of vitamins and minerals in complex drug to the increase of height and weight in children were included. Proved that routine prescription of micronutrients is accompanied by increase of children's height - standardized mean difference (smd) was 0,28 (95% ci - 0,09; 0,47) (р = 0,003). Maximal efficacy of micronutrients supply was registered in subgroup of stunted children with heightbage zbscores (haz) < b2,0 - SMD 0,58 (0,33; 0,84) (p < 0,001) and in children over 5 years - SMD 0,42 (0,07; 0,78) (р = 0,02). micronutrients don't affect body weight, HAZ, WAZ (weightbage zbscores) and WHZ (weight height zbscores). The results of trials were heterogeneous. The reasons of heterogeneity were a difference in age of children, growth and body weight dynamics, and duration of trial. This metabanalysis indicates that routine micronutrients supply doesn't affect children's body weight, but favors to increase of their growth compared to placebo. Micronutrients show maximal activity in stunted children.Key words: children, micronutrients, height, weight, meta analysis.